Rehabilitation and destination of a confiscated squirrel monkey (Saimiri collinsi) following conservationists guidelines: a case study - Soares, Paola Cardias; Lopes, Jessica Albuquerque; da Silva, Leila Menezes; Mesquita, Ellen Yasmin Eguchi; Ribeiro, Ana Sílvia Sardinha; Bezerra, Andréa Magalhães (Neotropical Primates, 2016)
No abstract